The Influence of Learning Models Core (Connecting, Organizing, Reflecting and Extending) to Critical Thinking Ability and Achievement Students of Grade V of Tritih Kulon 05 State Elementary School - Kartika Wahyuningsih; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to determine the effect of the CORE (Connecting, Organizing, Reflecting and Extending) Learning Model on students' critical thinking abilities and learning achievement. This research uses a quantitative experimental research type with a quasi-experimental method. The research sample in the VA class was 20 students as the experimental group and 21 students in the VB class as the control group. The data collection method uses the test method, 10 multiple choice questions to test learning achievement and 4 essay questions for critical thinking skills. Based on the results of data processing on the posttest scores through the Independent Sample T-test, the critical thinking ability variable showed a result of 0.03 < 0.05, meaning Ha was accepted. processing the posttest score data through the Independent Sample T-test for the learning achievement variable also showed a result of 0.00 < 0.05, meaning Ha was accepted. Thus, the CORE (Connecting, Organizing, Reflecting and Extending) Learning Model has a positive effect on students' critical thinking abilities and learning achievements.